Correlation of sonographic prostate volume with international prostate symptom score in South Indian men - NG, Basawaraj; Dasan, T. Arul; Patil, Savitha S (International Journal of Research in Medical Sciences, 2017)
Background: Benign prostatic hyperplasia (BPH) is a common disease in old age individuals, usually starts around the age of 40 years, the prevalence of benign prostatic hyperplasia rises to more than 50% at 50 years of age to as much as 90% at the age of 85 years. Proven BPH patients suffer from moderate to severe lower urinary tract symptoms (LUTS) that are symptoms related to storage and voiding of urine. This study was to determine relationship between sonologically measured prostate Volume and international prostate symptom score (IPSS). Methods: Clinically symptomatic 126 patients in the age group of 40-89 years were studied. All the patients underwent Transabdominal sonography for the estimation of prostate volume and clinical questionnaire for international prostate symptom score. Statistical Analysis by descriptive and analytical statistics using SPSS version 16. Chi-Square test used and P values ≤ 0.05 was considered to be statistically significant. Results: Among 126 individuals, The maximum number of patients, that is 45 patients had the prostate volume measuring 31-50 cc (35.7%), followed by 25 patients (19.8%) had the volume measuring more than 50 cc. Maximum number of patients 52 (41.3%) were having severe symptoms, 47 (37.3%) patients were having moderate symptoms and 27 patients symptoms and 27 patients (21.4%) were having mild symptoms. Prostate volume had statistically significant but weak correlation observed with IPSS (r=0.40, p=0.001), Weak Stream (r=0.31, p=0.001) and urgency (r=0.31, p=0.001). Conclusions: Prostate volume had statistically significant but weak correlation observed with IPSS.